2022
DOI: 10.3389/fmicb.2022.851424
|View full text |Cite
|
Sign up to set email alerts
|

Methanotrophs Contribute to Nitrogen Fixation in Emergent Macrophytes

Abstract: Root-associated aerobic methanotroph plays an important role in reducing methane emissions from wetlands. In this study, we examined the activity of methane-dependent nitrogen fixation and active nitrogen-fixing bacterial communities on the roots of Typha angustifolia and Scirpus triqueter using a 15N-N2 feeding experiment and a cDNA-based clone library sequence of the nifH gene, respectively. A 15N-N2 feeding experiment showed that the N2 fixation rate of S. triqueter (1.74 μmol h–1 g–1 dry weight) was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The 15 N and 13 C abundances in the freeze-dried soil were measured by a stable-isotope ratio mass spectrometer (Isoprime-100, Elementar). The BNF rates were calculated using the formula (SW × TN/100 × ( 15 N c1 – 15 N c2 )/ 15 N g × 100/MW/ t ) as previously described [ 17 ], where SW is the dried soil weight (1.00 g/reactor), TN is the average nitrogen content (%, w/w), and MW is the molecular weight (30) of 15 N 2 . The 15 N c1 and 15 N c2 represent the respective final and initial 15 N concentrations (atom% excess) in the soils, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The 15 N and 13 C abundances in the freeze-dried soil were measured by a stable-isotope ratio mass spectrometer (Isoprime-100, Elementar). The BNF rates were calculated using the formula (SW × TN/100 × ( 15 N c1 – 15 N c2 )/ 15 N g × 100/MW/ t ) as previously described [ 17 ], where SW is the dried soil weight (1.00 g/reactor), TN is the average nitrogen content (%, w/w), and MW is the molecular weight (30) of 15 N 2 . The 15 N c1 and 15 N c2 represent the respective final and initial 15 N concentrations (atom% excess) in the soils, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Another study also revealed that methanotroph inoculation on rice fields lowered CH 4 emissions by 60% and augmented rice yield by 35% [26]. The augmentation of rice yields, known as several methanotrophs, can increase the soil N availability, enhancing photosynthate allocation to grains [26,31,32]. However, these studies examined differences in chemical fertilizer dosages or types of methanotrophs.…”
Section: Effects Of Methanotroph-inoculated Bde On Methane and Nitrou...mentioning
confidence: 99%
“…Another study also revealed that methanotroph inoculation on rice fields reduced CH 4 emissions by 60% and increased the rice yield by 35% [26]. The augmentation of rice yields, known as several methanotrophs, can increase the soil N availability, enhancing photosynthate allocation to grains [26,31,32]. However, the studies above examined the potential of CH 4 emission reductions by inoculating methanotrophs on rice fields under the difference of fertilizer application dosages or fertilizer types, while fields amended with external organic carbon or higher dissolved organic carbon remains uncertain with methanotroph inoculation.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies have shown that soil methanotrophs contribute 10–20% to global methane consumption, playing a key role in methane balance [ 20 ]. The microhabitat of plants’ rhizosphere is closely linked to the methane oxidation process in soil, as methanotrophs are usually concentrated in the rhizosphere [ 21 , 22 ]. Oxygen is diffused from the roots into the plants’ rhizosphere and the adjacent soil through radial oxygen loss, creating a favorable microhabitat for aerobic methane oxidation [ 23 ].…”
Section: Introductionmentioning
confidence: 99%